Multimodal Smoking Cessation in a Real-Life Setting: Combining Motivational Interviewing With Official Therapy and Reduced Risk Products. (October 2019) - Caponnetto, Pasquale; DiPiazza, Jennifer; Cappello, Giorgio Carlo; Demma, Shirin; Maglia, Marilena; Polosa, Riccardo
Background: Tobacco use is a global pandemic, affecting an estimated 1.2 billion people and resulting in substantial health burdens and associated costs. Objectives: The aim of this study was to estimate the efficacy of several treatments for smoking cessation in a real-life setting and to evaluate predictors of smoking abstinence. Methods: This research was designed with a sample of 593 cases recorded over the period between 2015 and 2016. Six treatment groups were included: (1) bupropion and motivational interviewing (MI); (2) bupropion, nicotine replacement therapy (NRT), and MI; (3) NRT and MI; (4) varenicline and MI; (5) personal vaporizer electronic cigarette and MI; and (6) electronic cigarette, cigarette like "cigalike, " and MI. Results: Results support the efficacy of all treatment groups when used in a real-life setting. The predictors of smoking abstinence were sex, partner smoking status, previous quit attempts, daily consumption, self-efficacy, and level of nicotine dependence. Conclusions: The use of different therapeutic strategies in clinical practice, including pharmacotherapy and nonstandard electronic nicotine delivery systems, such as an electronic cigarette, ensures a greater chance of cessation success and the possibility of tailoring interventions according to patients' resources.